THE EFFECT OF FINANCIAL PERFORMANCE RATIOS ON CONVENTIONAL BANK PROFITABILITY IN INDONESIA STOCK EXCHANGE - Ahmad Azmy; Iqbal Febriansyah; Anita Munir (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2019)
This study aims to analyze the effect of the ratio of financial performance to the profitability of private conventional commercial banks listed on the Indonesia Stock Exchange. Retrieval of data using financial statements from fourteen conventional commercial banks. The independent variables used include Capital Adequacy Ratio (CAR), Operational Income Operating Expenses (BOPO), Non Performing Loans (NPL), and Loan to Deposit Ratio (LDR). The profitability variable is proxied by Return on Assets (ROA). This type of research is quantitative that uses secondary data. The analysis was carried out using multiple regression analysis. The results showed that, CAR and NPL had no effect on ROA, while BOPO and LDR had a significant effect on ROA. Then the F Test results show that CAR, NPL, BOPO, and LDR simultaneously influence ROA